Stakeholders use A4NH evidence from program evaluations to inform decisions that guide and support nutrition-sensitive programming and policies in Ethiopia - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
Policymakers in Ethiopia, informed by evidence from Transform Nutrition, a program funded by DFID and A4NH, were guided to redesign the Productive Safety Net Programme with the inclusion of specific nutrition elements to increase the potential for this program to improve maternal and child nutrition.